(untitled) - Dilek Gürçayir; Neziha Karabulut (University of Ostrava, 2022)
Aim: This study was carried out to determine quality of life in patients who have had colorectal cancer surgery. Design: A sequential explanatory mixed methods design was used. Methods: The study sample consisted of 120 patients who had had colorectal cancer surgery, met the inclusion criteria for the study, and agreed to participate in the study. In-depth interviews were conducted with 20 of the patients from the study sample. The quantitative data were collected using the "Introductory information form" and the The Functional Assessment of Cancer Therapy-Colorectal Version "FACT-C scale", while the qualitative data were collected using the "Introductory information form" and the "Semi-structured interview form". Results: The FACT-C scale total mean score of the patients was 100.95 (± 10.07) before the surgery and 88.90 (± 10.55) after the surgery. From the in-depth interviews performed with the patients, the factors affecting the patients' physical, mental, and social well-being after discharge from hospital were identified. Conclusion: According to the results of this research, following colorectal cancer surgery, the patients faced problems that affected their physical, mental, and social well-being, and their quality of life diminished.